Adoption of Sustainable Dairy Management Practices among Peri-urban Dairy Farmers in Odisha - Kamlesh Kumar Acharya; Ravinder Malhotra, R. Sendhil, T. K. Mohanty; Biswanath Sahoo (Indian Journal of Extension Education, 2022)
The research was based on a survey done in 2019 across Odisha’s eastern and southern coastal plain zones to assess sustainability among dairy farms based on various scientific management practices adopted by the farmers. The sustainability index was constructed using primary data acquired through a random sampling approach from 120 dairy households. The results reveal that 61 per cent of the farms belonged to the low sustainable category. The study area’s peri-urban dairy farms had inadequate shelter management, feeding, and animal health practices, as seen by their mean sustainable scores. Space constraints, dung disposal, lack of expertise in planned systematic breeding, paucity of green fodder, lack of refrigerated storage, and timely vaccination were all issues that farmers in the study area faced. These problems can be solved by organizing various capacity building training programmes, creating awareness about the benefits of following various scientific management practices, finding alternative supplements of green fodder as well as encouraging farmers to cultivate green fodder at a commercial level.